Identification of novel factors contributing to the regulation of PIN-FORMED 7 (PIN7) transcription, in the Arabidopsis root - Goodall, Benjamin (2018)
Understanding root development and patterning is important for both nutrient and water uptake. The Arabidopsis thaliana primary root has a di-arch vascular pattern consisting of a central xylem axis, perpendicular phloem poles and intervening procambial cells. Governance of this pattern involves a dynamic, antagonistic interaction between domains of auxin and cytokinin signalling bias. Here, one element of this auxin-cytokinin relationship; cytokinin’s indirect transcriptional regulation of the auxin PIN-FORMED 7 (PIN7) efflux transporter, has been investigated. Two complementary strategies were employed; transcriptomic profiling of an Type-B ARABIDOPSIS RESPONSE REGULATOR (ARR) response (the last known components in the core cytokinin signalling machinery) via an inducible glucocorticoid system, and an EMS mutagenesis based forward genetic screen of reduced PIN7::PIN7:GFP expression and subsequent genomic resequencing to identify potential causative agents. Both workflows produced novel candidate PIN7 regulators and the ensuing candidate validation revealed ETHYLENE RESPONSE FACTOR 104 (ERF104), CYTOKININ OXIDASE/DEHYDROGENASE 5 (CKX5) and the ECA1-like AT5G36520 from its vascular over-expressor DOUBLE PROTOXYLEM (DPX) phenotype, in particular as strong contenders for components involved in the regulation of PIN7 and patterning of the vascular cylinder.